The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1111/j.1600-0765.1978.tb00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Collagen turnover in the periodontal ligament under normal and altered functional forces

Abstract: 48 six month old rats were given 1 μCi/g of body weight of tritiated proline by intraperitoneal injection, 24 of them having had the left maxillary molars extracted two weeks earlier; 4 animals from each group were killed after a further 12 hours, 1, 4, 7, 12 or 20 days. Analyses of autoradiographic grain densities in various areas of the lower first molar periodontal ligament allowed calculation of half‐lives which were attributable to collagen turnover; all such values were less than 12 days. It is argued th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 22 publications
4
38
0
Order By: Relevance
“…Schneir et al (1976) examining the palatal antemolar mucosa in rats between 17 and 680 days of age found an age-dependent decrease in the rate of collagen synthesis. For 42-day old rats, Rippin (1976) demonstrated a high turnover of collagen in the crestal portion of the periodontal ligament, a site which is topographically close to the supraalveolar attached gingiva portion. The present data suggest that fibroblasts residing in this supraalveolar attached portion of the gingiva, although remaining constant in number over the age period from 30 to 80 days, are maximally large around the age of 40 days, at least in the facial and interdental gingiva, but furtheron decrease in size considerably.…”
Section: Discussionmentioning
confidence: 95%
“…Schneir et al (1976) examining the palatal antemolar mucosa in rats between 17 and 680 days of age found an age-dependent decrease in the rate of collagen synthesis. For 42-day old rats, Rippin (1976) demonstrated a high turnover of collagen in the crestal portion of the periodontal ligament, a site which is topographically close to the supraalveolar attached gingiva portion. The present data suggest that fibroblasts residing in this supraalveolar attached portion of the gingiva, although remaining constant in number over the age period from 30 to 80 days, are maximally large around the age of 40 days, at least in the facial and interdental gingiva, but furtheron decrease in size considerably.…”
Section: Discussionmentioning
confidence: 95%
“…This inference is in accordance with the work of Kanoza et al (1980), who found that in the rat periodontal ligament the rate of synthesis and deposition of collagen doubled three days after extraction of the opposing molars. Also, Rippin (1976Rippin ( , 1978, in a radioautographic study of overall protein turnover in periodontal ligaments from normal and hypofunctional rat molars, noted an increase of turnover in the crestal portion of the latter.…”
Section: Discussionmentioning
confidence: 95%
“…The metabolic activity of the periodontal ligament also seems to depend on location. The areas adjacent to the alveolar bone have a rapid turnover (77, 93, 1661, and collagen half-lives differ between the apical and crestal regions of the periodontal ligament (116,126,127). The rate of turnover of the different collagen types is not known, but studies have demonstrated that the metabolism of types I and I11 collagen appears to be similar (158,159).…”
Section: Periodontal Ligamentmentioning
confidence: 99%